an Urgent Call for Suicide Prevention in Indonesia: The Clinicians’ Role in Preventing Suicide - Alshafiera Azayyana Mawadhani Sukma; Adi Winata; Balatif, Ridwan (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: Since suicide is a complicated matter, multiple sectors must be involved. Globally, there were 703,000 suicide cases in 2019. Over the past three years, there has been a rise in suicide instances in Indonesia. Treating those who are at risk of suicide is difficult since suicide situations, like mental health illnesses, continue to carry stigma. To provide a statistical overview of suicide cases and the role of clinicians in preventing suicide cases. Methods: Searching for statistical data in Indonesia, we used Pubmed with the keyword “statistics”, “suicide”, “Indonesia”. Searching for data regarding risk factors and prevention of suicide, we also used Pubmed with the keywords “risk factor”, “prevention”, “screening”, “suicide”. Results: Globally, in 2019 the average rate of suicide cases was around 9.0 cases per 100,000 population. In Indonesia, exact data regarding the prevalence of suicide cases is still unknown. A person committing suicide can be caused by many factors such as previous mental disorders, relationship conflicts, legal problems, violence, financial problems, social exclusion, and low socioeconomic status. In addition to providing appropriate management, a clinician must provide education and outreach to the public regarding warning signs and risk factors for suicide, restrictions on tools for suicide, screening, and also remind every patient, especially patients with mental disorders, to continue to pray to be given health. Conclusion: A clinician has a role ranging from education and related outreach, screening, and also pharmacological and non-pharmacological management of someone at risk of suicide